2021
DOI: 10.1111/soin.12412
|View full text |Cite
|
Sign up to set email alerts
|

Sticking to Their Guns: Examining Firearm‐Related Protective Actions among Intimate Partner Violence Victims

Abstract: An abusive partner's access to a firearm is one of the strongest predictors of intimate partner homicide, and there is evidence that laws limiting abusers' access to firearms are associated with fewer fatalities. Yet, there is a movement to increase access to firearms as a strategy for self-protection among intimate partner violence (IPV) victims. The present study describes both firearm-related and non-firearm-related protective actions among victims of IPV, and further examines which factors (e.g., pro-gun a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…That is why in the study of Wu and Klahm [113], women were found to take more precautionary measures and strategies compared to men. They were also most likely to own firearms or other weapons for self-defense, especially when faced with violent and dangerous environments [114]. With those findings, it could be implied that women would splurge more to ensure their safety.…”
Section: Discussionmentioning
confidence: 90%
“…That is why in the study of Wu and Klahm [113], women were found to take more precautionary measures and strategies compared to men. They were also most likely to own firearms or other weapons for self-defense, especially when faced with violent and dangerous environments [114]. With those findings, it could be implied that women would splurge more to ensure their safety.…”
Section: Discussionmentioning
confidence: 90%
“…Following separation, survivors and their children typically engage with legal systems. When threatened with firearms, survivors may choose to seek a civil protective order as a safety strategy (Kafka et al., 2021; Lynch, Boots, et al., 2022; Lynch, Jackson, et al., 2022). Family courts are the central legal context that regulates the custody of children following parental separation.…”
Section: Introductionmentioning
confidence: 99%
“…Threats may be spoken verbally or communicated over technology (e.g. text, email and social media), through hostile gun displays (Azrael & Hemenway, 2000), or more covert tactics such as cleaning a gun in front of a survivor to send a message (Lynch, Boots, et al., 2022; Lynch, Jackson, et al., 2022).…”
Section: Introductionmentioning
confidence: 99%